Optimal. Leaf size=26 \[ 2 e^{e^x-\frac {5}{5+5 (-3+x)}-x}-x \]
________________________________________________________________________________________
Rubi [F] time = 8.09, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {e^{-\frac {1+e^x (2-x)-2 x+x^2}{-2+x}} \left (-6+8 x-2 x^2+e^{\frac {1+e^x (2-x)-2 x+x^2}{-2+x}} \left (-4+4 x-x^2\right )+e^x \left (8-8 x+2 x^2\right )\right )}{4-4 x+x^2} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {e^{-\frac {1+e^x (2-x)-2 x+x^2}{-2+x}} \left (-6+8 x-2 x^2+e^{\frac {1+e^x (2-x)-2 x+x^2}{-2+x}} \left (-4+4 x-x^2\right )+e^x \left (8-8 x+2 x^2\right )\right )}{(-2+x)^2} \, dx\\ &=\int \left (-1+2 e^{e^x+\frac {1}{2-x}}-\frac {2 e^{e^x-\frac {(-1+x)^2}{-2+x}} \left (3-4 x+x^2\right )}{(-2+x)^2}\right ) \, dx\\ &=-x+2 \int e^{e^x+\frac {1}{2-x}} \, dx-2 \int \frac {e^{e^x-\frac {(-1+x)^2}{-2+x}} \left (3-4 x+x^2\right )}{(-2+x)^2} \, dx\\ &=-x+2 \int e^{e^x+\frac {1}{2-x}} \, dx-2 \int \left (e^{e^x-\frac {(-1+x)^2}{-2+x}}-\frac {e^{e^x-\frac {(-1+x)^2}{-2+x}}}{(-2+x)^2}\right ) \, dx\\ &=-x+2 \int e^{e^x+\frac {1}{2-x}} \, dx-2 \int e^{e^x-\frac {(-1+x)^2}{-2+x}} \, dx+2 \int \frac {e^{e^x-\frac {(-1+x)^2}{-2+x}}}{(-2+x)^2} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.40, size = 22, normalized size = 0.85 \begin {gather*} 2 e^{e^x-\frac {1}{-2+x}-x}-x \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.62, size = 29, normalized size = 1.12 \begin {gather*} -x + 2 \, e^{\left (-\frac {x^{2} - {\left (x - 2\right )} e^{x} - 2 \, x + 1}{x - 2}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [F] time = 0.00, size = 0, normalized size = 0.00 \begin {gather*} \int -\frac {{\left (2 \, x^{2} - 2 \, {\left (x^{2} - 4 \, x + 4\right )} e^{x} + {\left (x^{2} - 4 \, x + 4\right )} e^{\left (\frac {x^{2} - {\left (x - 2\right )} e^{x} - 2 \, x + 1}{x - 2}\right )} - 8 \, x + 6\right )} e^{\left (-\frac {x^{2} - {\left (x - 2\right )} e^{x} - 2 \, x + 1}{x - 2}\right )}}{x^{2} - 4 \, x + 4}\,{d x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.23, size = 32, normalized size = 1.23
method | result | size |
risch | \(-x +2 \,{\mathrm e}^{\frac {{\mathrm e}^{x} x -x^{2}-2 \,{\mathrm e}^{x}+2 x -1}{x -2}}\) | \(32\) |
norman | \(\frac {\left (-4+4 \,{\mathrm e}^{\frac {\left (2-x \right ) {\mathrm e}^{x}+x^{2}-2 x +1}{x -2}}+2 x -x^{2} {\mathrm e}^{\frac {\left (2-x \right ) {\mathrm e}^{x}+x^{2}-2 x +1}{x -2}}\right ) {\mathrm e}^{-\frac {\left (2-x \right ) {\mathrm e}^{x}+x^{2}-2 x +1}{x -2}}}{x -2}\) | \(90\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.63, size = 20, normalized size = 0.77 \begin {gather*} -x + 2 \, e^{\left (-x - \frac {1}{x - 2} + e^{x}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 0.82, size = 54, normalized size = 2.08 \begin {gather*} 2\,{\mathrm {e}}^{\frac {x\,{\mathrm {e}}^x}{x-2}}\,{\mathrm {e}}^{\frac {2\,x}{x-2}}\,{\mathrm {e}}^{-\frac {x^2}{x-2}}\,{\mathrm {e}}^{-\frac {2\,{\mathrm {e}}^x}{x-2}}\,{\mathrm {e}}^{-\frac {1}{x-2}}-x \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.35, size = 22, normalized size = 0.85 \begin {gather*} - x + 2 e^{- \frac {x^{2} - 2 x + \left (2 - x\right ) e^{x} + 1}{x - 2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________